Pedagogical conditions of future teachers of preschool education to work with children with functional disorders of the musculoskeletal system (Pedagogy of Higher and Secondary Education, 2013)
Shovkoplyas O.M. Pedagogical conditions of future teachers of preschool education to work with children with functional disorders of the musculoskeletal system.This paper deals with determination of the necessary educational conditions for the efficient process of formation of future teachers to work with preschool children with functional disorders opine motor system.
Keywords: teaching conditions; future educators; preschool children